Paralinguistics, Community and the Rhetoric of Division in Attic Oratory (Circe de clásicos y modernos, 2022)
The study of paralinguistics, i.e. the ways of communicating without the use of language, whether conscious, intentional and voluntary or otherwise, is an essential component of any attempt to reconstruct, understand and interpret the systems of cultural, societal, institutional, moral and inter-personal communication in modern and ancient societies. Three specific aspects of paralinguistics, as they are described in Attic oratory, are examined in this paper: face and facial organs (such as mouth and nose), hands, and gait. It is argued that the references to paralinguistics aim to win over the audience in the lawcourt or in political conventions by arousing emotions and by sustaining a war between the speaker’s opponents and the Athenian community, whose cultural values and beliefs the opponents are presented as violating.
Keywords: Paralinguistics; community; division; emotions